Hans Ulrich Obrist: Interview with Susan Hefuna- Alexandria Contemporary Arts Forum 2008 - Hefuna, Susan (3ShRGf Mahfgs; Obrist, Hans Ulrich (Heidelberg; Kehrer Verlag, 2008)
Published on the occasion of the exhibition 'Susan Hefuna- Knowledge is sweeter than honey' Feb-March 2008. Interview with artist. Exhibition @Alexandria Contemporary Arts Forum, ACAF
English; Arabic
Keywords: N4390-5098 Visual Arts. Exhibitions